Book Review. (1st July 2018) - Laforcade, Geoffroy de
Abstract : Amzat Boukari-Yabara's portrait of Guyanese scholar and activist Walter Rodney (Walter Rodney: Un historien engagé, 1942-1980, Paris: Présence Africaine, 2018) is not a traditional biography, but rather a narrative of the context in which he deployed his work as an historian and a politically engaged contributor to African and Caribbean studies in the 1960s and 1970s. The author, like Rodney himself, believes that the history of African and Afro-diasporic peoples should be written from the Africas and the Americas themselves. Whether writing about the history of the slave trade, the African past, decolonization or black power, the biographer expertly conveys Rodney's erudition while directing students of these issues toward a broader retrospective, contextualization and actualization of his thought. More than any existing biography or chronicle of Rodney's life, it is a book that redefines and actualizes what it means to be an "historien engagé, " a politically and socially committed student of the past and its lessons for the present.